Paul Green's Wordbook An Alphabet of Reminiscence - Green, Paul (Appalachian State University, 1990)
Paul Green's Wordbook: An Alphabet of Reminiscence, the culmination of more than sixty years of observing and collecting superstitions, customs, cures, riddles, games, stories, songs, and beliefs, was published in 1990. A personal collection of folk traditions, Paul Green thought that these common idioms served to showcase the heritage of mankind. With roots in eastern North Carolina, Green took inspiration from his peers to write down the traditions of his home state in 1600 pages. The first rendition of Paul Green's Wordbook was released in March 1937 by the University of North Carolina at Chapel Hill, and tentatively titled Folk Beliefs and Practices in Central and Eastern North Carolina 1926-28. It took Green most of his life to revise the wordbook until it was in its final state in 1990.